Peran Sosial Media Marketing dalam Perkembangan Usaha Air Minum dalam Kemasan (Studi Kasus pada Air Minum Arcos) - Raisya Salsabilla; Fazilla Amalia; Aisyah Sri Wahyuni; Efti Novita Sari (Prosiding Seminar Nasional Manajemen dan Ekonomi, 2023)
This study aims to analyze the role of social media marketing in the development of the Arcos Packaged Drinking Water (AMDK) business. By using in-depth interviews with Arcos management and marketing teams, this study reveals how digital marketing strategies, especially through social media such as Instagram, Facebook, and Twitter, play an important role in increasing brand awareness, market reach, and consumer loyalty. The results of the study show that collaboration with influencers, the use of attractive visual content, and active interaction with consumers through social media have had a significant positive impact on sales growth. In addition, the ability of social media to enable real-time interaction with consumers helps companies to dynamically adjust their marketing strategies and respond to market needs more effectively. However, this study also notes challenges, especially related to competition in the packaged drinking water industry. This study concludes that social media marketing is a very effective and efficient tool for developing a business, but it requires a creative strategy and continues to adapt to changes in digital trends. Recommendations for future research are to explore newer social media platforms, combine qualitative and quantitative research methods, and conduct comparative studies with other brands in similar industries.